The creative corner / Aina Syasya Arifin ... [et al.] - Arifin, Aina Syasya; Murad, Reza; Aboo Bakar, Rofiza; Ahmad Zubir, Hanani; Mohd Amin, Noraziah; Zulkifli, Che Nooryohana (Academy of Language Studies, 2021)
*Breathe *The Lost Traveler *Dua Puluh Lima Tahun, UiTMku *Satria Pujaan *Bendera Putih *Bukan Main Lagi *You and Your Giant Fist! *Yeop and Rendang